Literature Review: The Efficacy of Kangaroo Mother Care (KMC) On Weight Gain In Low Birth Weight (LBW) Infants - Diyanariyah, afsnur; Angryni, Ria; Hani, Siti; Trimawati (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Low Birth Weight (LBW) infants represent a highly vulnerable group with elevated mortality rates due to physiological immaturity, particularly regarding thermoregulation stability. Deficient fat reserves render these infants susceptible to rapid heat loss, forcing the body to expend excessive energy merely for survival, which subsequently hinders weight gain. Kangaroo Mother Care (KMC) serves as a critical intervention that utilizes maternal body heat to stabilize infant temperature. By achieving normothermia, nutritional energy can be maximized for cellular growth, leading to faster and more optimal weight gain compared to conventional care. This literature review aims to comprehensively evaluate the efficacy of KMC implementation in stimulating accelerated weight gain among LBW infants. The primary focus is to identify the extent to which skin-to-skin contact interventions provide significant clinical contributions to physical stability and neonatal growth. A comprehensive literature review was conducted on eight scientific articles published between 2022 and 2025. Data were extracted from credible national and international databases using strict inclusion criteria. The evaluation process involved analyzing intervention duration parameters and comparing clinical outcomes across studies to produce a valid data synthesis. Synthesis of the literature confirms that consistent KMC implementation significantly impacts daily weight gain positively. Key findings indicate that long-duration interventions (at least 8 hours per day) result in superior growth outcomes compared to short-duration care. Furthermore, this method is clinically proven to enhance the success of exclusive breastfeeding, which acts as a primary determinant in meeting nutritional needs and increasing infant body mass. The conclusion of this study was kangaroo Mother Care is a highly effective, safe, and cost-efficient intervention strategy for optimizing the physical recovery of LBW infants. In addition to its benefits for weight growth, this method has clinical significance in reducing the duration of hospitalization, making it strongly recommended for integration as a standard in neonatal nursing care.